2017
DOI: 10.1177/1460408617700450
|View full text |Cite
|
Sign up to set email alerts
|

Do clinical guidelines for whole body computerised tomography in trauma improve diagnostic accuracy and reduce unnecessary investigations? A systematic review and narrative synthesis

Abstract: Introduction: Whole body computerised tomography has become a standard of care for the investigation of major trauma patients. However, its use varies widely, and current clinical guidelines are not universally accepted. We undertook a systematic review of the literature to determine whether clinical guidelines for whole body computerised tomography in trauma increase its diagnostic accuracy. Materials and methods: A systematic review of Medline, Cinhal and the Cochrane database, supplemented by a manual searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Male and female patients of all ages with suspected blunt multiple trauma presenting to the emergency department and assigned to WBCT according to red flag criteria of the national evidence- and consensus-based best practice guideline for managing patients with severe injuries (Box) were eligible to participate in the study . Indication for WBCT matched international recommendations as summarized in recent systematic reviews . Patients were approached, informed about the study, and asked for consent to participate as soon as allowed by their physical and mental condition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Male and female patients of all ages with suspected blunt multiple trauma presenting to the emergency department and assigned to WBCT according to red flag criteria of the national evidence- and consensus-based best practice guideline for managing patients with severe injuries (Box) were eligible to participate in the study . Indication for WBCT matched international recommendations as summarized in recent systematic reviews . Patients were approached, informed about the study, and asked for consent to participate as soon as allowed by their physical and mental condition.…”
Section: Methodsmentioning
confidence: 99%
“…21 Indication for WBCT matched international recommendations as summarized in recent systematic reviews. [22][23][24][25][26] Patients were approached, informed about the study, and asked for consent to participate as soon as allowed by their physical and mental condition. Relatives, legal representatives, and patients were informed by physicians or professional clinical trial staff.…”
Section: Selection Of Participantsmentioning
confidence: 99%
“…The alternative to immediate SWBCT as a screening for injuries would be a clinical decision tool providing evidence based selection criteria for CT examination strategy decision. Hare et al [70] reviewed the literature to clarify whether such tools improve diagnostic accuracy of whole body CT, and concluded that the evidence to support this is limited. All identified studies were retrospective analyses of predictors for CT findings [32,34,65,71].…”
Section: Discussionmentioning
confidence: 99%